An investigation of academic perspectives on the 'circular economy' using text mining and a Delphi study. (15th October 2021) - Mahanty, Sampriti; Boons, Frank; Handl, Julia; Batista-Navarro, Riza
Abstract: The Circular Economy (CE) concept has received immense traction among various stakeholders. This study aims to provide an assessment of its evolution and its positioning amidst "competing" concepts in the academic discourse. We do so by a mixed-methods approach combining text mining (topic modelling on CE literature) and Delphi study with 68 international scholars. In its evolution, we observe a structural change in the years 2014–2015 characterised by CE research undergoing immense proliferation, adopting a distinct line of inquiry from industrial ecology, becoming dispersed across topics and shifting from macro to micro-level interventions. This change is attributed to the use of CE to denote ideas and practices that existed before, increased interest from policymakers, adoption of CE terminology by businesses, and the research cycle of the concept itself shifting from being exploratory into different areas of practical implementation. In its positioning, we observe that scholars use several other "competing" concepts along with CE and do not consider it dominant despite the immense attention. The reason being, mainstream CE research is largely focussed on resource flows with limited attention to some of the long-term environmental challenges and it also overlooks the social dimension of sustainability, notwithstanding the efforts to make it inclusive. This study provides further impetus to academic knowledge on CE by a combination of quantitative analysis with a systematic, expert-based interpretive assessment of the literature. The enumeration of a wide range of concepts used by scholars provides an overview and a conceptual toolkit to researchers and newcomers to the field. This study also provides a set of informed future research avenues based on the expert assessment. The methodological contribution is of additional value to the research community. Graphical abstract: Image 1 Highlights: Assessing the evolution and positioning of Circular Economy (CE) in academic research. A mixed methods approach combining text mining (topic modelling) and Delphi study. Longitudinal analysis of the literature taking into account 3300 academic articles. Opinion of 68 international experts to investigate the CE's position and evolution. Future research avenues are suggested based on the assessment of the experts.